IMPLEMENTASI MANAGEMEN PENDIDIKAN ISLAM PADA DOSEN PERGURUAN TINGGI ISLAM DI ERA PANDEMI COVID 19 - Rahayu, Sucik; Rossari, Dwi Vianita; Wangsanata, Susana Aditiya; Saputri, Nuriana Eka; Saputri, Nuriani Dwi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The pandemic has indeed had a fairly bad impact, especially for the world of education in Indonesia, but this did not shake Indonesia, with the assistance of highranking officials to rise on the footing of the various efforts that have been deployed. In a pandemic like this, the number of students per campus has decreased significantly. So that various ways and efforts are needed to attract their interest in learning. One way is to implement Islamic education management in which there are various best programs that can be implemented to improve the quality and image of the university itself. Although there are several obstacles, in its implementation it has been proven to have a good influence on the education system in the era of the covid-19 pandemic